The Clinton Administration's Vision for Economic Development - Tyson, Laura (Maine Policy Review, 1993)
The 20th anniversary of the Governor’s Economic Development Conference last October focused on the impact of public policy on the competitiveness of Maine’s business and industry. Among many other important presentations, the University of Maine-sponsored conference featured a televideo keynote address by the Clinton Administration’s top economic adviser, Laura D’Andrea Tyson. Tyson’s remarks, which detailed the Administration’s policy initiatives meant to enhance the nation’s competitiveness relative to the international economy, are presented in this article.
Keywords: public policy; economic development; healthcare reform; NAFTA